The Migration of Constitutional Ideas - Choudhry, Sujut (Cambrigde University Press, 2013)
This idea for this book emerged in the way that the best ideas do – in scholarly conversation. The migration of constitutional ideas has emerged as one of the dominant features of contemporary constitutionalism. For my colleagues at the University of Toronto, this shift in constitutional practice has meant that sustained and deep comparative engagement increasingly permeates our research and teaching